Minimizing morphological defects of PEI hollow fibre membrane by optimizing the dope viscosity - Jamil, A. (Asian Research Publishing Network, 2016)
Phase inversion processes have been used to fabricate hollow fibre membranes but these processes often lead to morphological defects such as formation of macrovoids. Thus far, several approaches have been investigated to solve this problem, but no consensuses have been achieved. In this study, the optimal dope viscosity for PEI/NMP solution was elucidated to produce improved membrane morphological structure that can enhance its gas separation performance. Five concentrations of PEI/NMP dope solutions were prepared and their viscosities were measured. The critical viscosity was found to be at approximately 25 wt. polymer concentration at ambient conditions. SEM analysis revealed that the most uniform finger-like pores with a thin skinned upper layer was obtained at critical dope viscosity. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.